PENGGUNAAN MEDIA TEKA-TEKI SILANG BERGAMBAR BERBASIS CERITA TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS III SEKOLAH DASAR - Novianti, Alifia Ayu; Wati, Tri Linggo (STKIP Persada Khatulistiwa Sintang, 2025)
This study aims to introduce a picture-based crossword puzzle media integrated with storytelling to support learning activities that enhance students’ reading comprehension skills. The research employed a quantitative approach with a Pre-Experimental method using a One-Group Pretest–Posttest Design. The population consisted of third-grade students at SDN Lebo Sidoarjo, with a sample of 38 students. Data were collected through interviews and tests, which included pretest and posttest instruments. The data analysis technique utilized the Wilcoxon Signed Ranks Test with the assistance of IBM SPSS Statistics. The results showed that the picture-based crossword puzzle media based on storytelling had a significant influence on students’ reading comprehension, as indicated by a p-value of 0.046 (< 0.05) and an improvement in posttest scores compared to pretest results. Therefore, this study concludes that the picture-based crossword puzzle media integrated with storytelling is feasible and effective as an alternative learning medium to enhance reading comprehension among elementary school students.